Customer-based brand equity for a tourism destination: The case of Croatia - Lenka Cervova; Jitka Němečková Vávrová (Economies, 2021)
Tourism has been negatively impacted by the global COVID-19 pandemic, making it even more important for tourist destinations to focus on their brand equity from the perspective of their customers-visitors. The aim of this paper is therefore to verify and modify the model of customer-based brand equity for a tourism destination (CBBETD) and its attributes for the destination of Croatia from the perspective of Czech tourists, among whom primary research was conducted using the CAWI method (n = 451). The main CBBE dimensions were extracted using factor analysis and a model with four dimensions (awareness, image, quality and loyalty) was created. The identified attributes explain between 55% and 82% of the variability of a given dimension. Although the study's results follow the published models of CBBETD, the attributes in each dimension and the subdimension in the image dimension reflect the specificities of the destination of Croatia. Thus, the results of this paper extend the economic theory with another model and are also applicable in the field of destination management.
Keywords: 330; brand equity; Croatia; customer-based brand equity; destination; destination awareness; destination brand; destination image; destination loyalty; destination management; destination quality; tourism; visitors' loyalty